1982
DOI: 10.1002/art.1780251004
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes in progressive systemic sclerosis (scleroderma)

Abstract: Serum immune complexes were measured in 92 patients with progressive systemic sclerosis, and elevated levels were found as follows: Raji cell assay 72% (59% after pronase treatment of Raji cells), agarose gel electrophoresis 52%, and Clq binding 24%. Fortythree (47%) had abnormal results on two or more of these tests, but only 17 (18%) had normal results by all three assays. Computer-assisted analysis of immune complex results and extensive clinical and laboratory data compiled on these patients revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…However, both Seibold et al 35 and Benbassat et al 36 found hypocomplementaemia in 12% and 22.5% respectively—that is, in percentages not different from that detected by us (14%).…”
Section: Discussioncontrasting
confidence: 48%
“…However, both Seibold et al 35 and Benbassat et al 36 found hypocomplementaemia in 12% and 22.5% respectively—that is, in percentages not different from that detected by us (14%).…”
Section: Discussioncontrasting
confidence: 48%
“…However, several early studies have reported abnormal complement activation and subendothelial deposition of immune complexes in patients with SSc [90,91]. Batal et al investigated renal histology in scleroderma renal crisis.…”
Section: The Complement System and Systemic Sclerosismentioning
confidence: 99%
“…This may result from endothelial damage mediated by immunological processes. Although circulating immune complexes are not considered as a major factor in the pathogenesis of scleroderma, increased levels have been described in MCTD and scleroderma.25 26 Autoantibodies may be pathogenic either by participation in immune complexes, by antibody-dependent cytotoxicity, or by in-vitro penetration of living cells, as is especially observed for nRNP antibodies.27 The decreased capillary density and increased number of enlarged loops in patients with immunological abnormalities argues for immunologically mediated vascular disease. Immunological processes may result in local inflammation.…”
Section: Nailfold Capillary Findings and Organ System Involvementmentioning
confidence: 99%